Vasospastic Angina and Ca Channel Blockers - Minatoguchi, Shinya (Current Hypertension Reviews, 2013)
Coronary artery spasm is one of the causes of angina pectoris,acute myocardial infarction and ventricular fibrillation-related sudden death. It has been established that Ca channel blockers are protective against vasospastic angina (VSA) and treatment with Ca channel blockers provides a better prognosis of VSA. However, it is not still clarified what kinds of Ca channel blockers shows the best prognosis of VSA. We performed a meta-analysis in which 4Ca channel blockers amlodipine, nifedipine, benidipine and diltiazem were used for the treatment of VSA patients and found that among 4 Ca channel blockers, benidipine showed a statistically significant better prognostic effect on MACE than amlodipine, nifedipine or diltiazem.
Keywords: vasospastic angina